The Role of Social Media Coordinator and Reporter In Management of Enjoy Semarang Section In Tribun Jateng Website - Ramadhan, Maulana; Pradekso, M.Sc, Drs. Tandiyo (Interaksi Online, 2017)
The development of information technology has encouraged Tribun Jateng newspaper to form the website named jateng.tribunnews.com. There are various sections included in the website; one of them is travel section called Enjoy Semarang. In its management, Enjoy Semarang section does not work very well in attracting its visitors or viewers. Based on the observation, the number of Enjoy Semarang visitors is only about 1392 visitors. Moreover, the content included in the news does not represent the name and the region of where Tribun Jateng comes from. The published news on the website is mostly derived by copying news from the other incorporated media or adapting news from foreign media. Because of that reasons, there is some travel news that contains information from outside Semarang, Central Java or even Indonesia. Besides its content, the distribution of the news through social media has not been optimized yet. Online Tribun Jateng has three social media accounts; they are Facebook, Twitter, and Instagram. With regard to the distribution through social media, Tribun Jateng does not use a specific method so that most of the news is published in the same way. As we can see, tourism as one of the most interesting topics is potential to attract the website visitors. We have incorporated with Tribun Jateng to manage this section. This management is intended to provide new and original news and to share information about tourism world and culinary in Semarang and Central Java through Enjoy Semarang section that can be accessed by the public. Besides, we also have handled the editorial and the social media management to distribute news from Enjoy Semarang section which has now been renamed the Travel section. The total number that can be gotten from Tribun Jateng Travel section is 13,000 per two months. This number is more than the minimal target which is 4,329 visitors. Within a day, the number of the obtained traffic has reached 900 visitors. Tribun Jateng team has also succeeded in making 316 news which is higher than minimum target, 300 news for two months. During the project, Tribun Jateng Travel team has also succeeded in making two social media accounts; Instagram travel specialization and Line. Those two accounts have reached its target within 800 total followers. Travel section like Tribun Jateng Travel has huge potential to get a large number of visitors. The priority is to keep the quality of the news in order not to lose the visitors. The rise of the traffic number will impact on the existence of online media